Prognostic value of quality-of-life scores in patients with breast cancer undergoing preoperative chemotherapy. Issue 1 (26th November 2018) - Takada, K; Kashiwagi, S; Fukui, Y; Goto, W; Asano, Y; Morisaki, T; Takashima, T; Hirakawa, K; Ohira, M
Abstract: Background: Recently, evaluation of quality of life (QOL) has been recognized as a significant outcome measure in the treatment of several cancers. In this study, the Anti-Cancer Drugs–Breast (ACD-B) QOL score was used to assess disease-specific survival in women with breast cancer undergoing preoperative chemotherapy (POC). Methods: QOL-ACD-B scores were evaluated before and after POC. The cut-off value of QOL-ACD-B contributing to events such as relapse or death was calculated by receiver operating characteristic (ROC) curve analysis. Results: In 300 women with breast cancer treated with POC, QOL was significantly reduced ( P < 0·001). A high QOL-ACD-B score before POC was an independent factor in the multivariable analysis of overall survival (hazard ratio 0·26, 95 per cent c.i. 0·04 to 0·96). Conclusion: Evaluation by QOL-ACD-B before POC may be useful to predict the prognosis of patients with breast cancer undergoing POC. Graphical Abstract: In women with breast cancer treated with preoperative chemotherapy (POC), evaluation by Quality of Life Questionnaire for Cancer Patients Treated with Anti-Cancer Drugs-Breast (QOL-ACD-B) before POC may be a useful index to predict prognosis after POC treatment.